Slow Deep Breathing: Non-Pharmacological Strategies in ControllingDiabetes Mellitus Risk Factors - Exsos Grend Dais; Tati Suryati; Maryati Maryati; Achirman Achirman; Ratna Sari Dinaryanti; Yanti Riyantini (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Diabetes mellitus (DM) is a major non-communicable disease with a continuously increasing global prevalence. Psychological stress is a modifiable risk factor associated with impaired glucose regulation; however, public awareness of stress management remains limited. This study aimed to determine the effect of structured deep breathing education on adults' deep breathing skills as a non-pharmacological approach to support DM risk reduction. A quasi-experimental study with a one-group pretest-posttest design was conducted among 43 adults selected through purposive sampling in Kebayoran Lama Selatan, South Jakarta. Participants received education and guided practice in slow deep breathing, and their skills were assessed using an observation checklist before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The median skill score increased from 26 (Q1–Q3: 25–31) before the intervention to 40 (Q1–Q3: 31–43) after the intervention. A statistically significant improvement was observed (Z = −4.863, p < 0.001), with a large effect size (r = 0.742). Structured deep breathing education significantly improved participants' ability to perform the technique correctly. These findings suggest that deep breathing education may serve as a simple complementary nursing intervention to support stress management as part of DM risk reduction strategies.